An ultraviolet photoacoustic spectroscopy study of the interaction between Lys49-phospholipase A(2) and amphiphilic molecules - Bugs, Milton Roque; Bortoleto-Bugs, Raquel Kely; Cornelio, Marinonio Lopes; Ward, Richard John (Elsevier B.V., 2007)
We have used near ultraviolet photoacoustic spectroscopy (PAS) over the wavelength range 240-320 nm to investigate the complex formed between the homodimeric bothropstoxin-I, a lysine-49-phospholipase A(2) from the venom of Bothrops jararacussu (BthTx-I), with the anionic amphiphile sodium dodecyl sulfate (SDS). At molar ratios > 10, the complex developed a significant light scatter, accompanied by a decrease in the intrinsic tryptophan fluorescence intensity emission (ITFE) of the protein, and an increase in the near UV-PAS signal. Difference PAS spectroscopy at SDS/BthTx-I ratios < 8 were limited to the region 280-290 nm, suggesting initial SDS binding to the tryptophan 77 located at the dimer interface. At SDS/BthTx-I ratios > 10, the intensity between 260 and 320 nm increases demonstrating that the more widespread tyrosine and phenylalanine residues contribute to the SDS/BthTx-I interaction. PAS signal phase changes at wavelengths specific for each aromatic residue suggest that the Trp77 becomes more buried on SDS binding, and that protein structural changes and dehydration may alter the microenvironments of Tyr and Phe residues. These results demonstrate the potential of near UV-PAS for the investigation of membrane proteins/detergent complexes in which light scatter is significant. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: photoacoustic spectroscopy; bothropstoxin-I; difference spectroscopy; fluorescence